Trials and Tribulations with VH Replacement - Meng, Wenzhao; Jayaraman, Sahana; Bochao, Zhang; Schwartz, Gregory W.; Daber, Robert; Hershberg, Uri; Garfall, Alfred; Carlson, Christopher S.; Luning Prak, Eline T. (Frontiers in Immunology, 2014)
VH replacement is a type of antibody gene rearrangement in which an upstream heavy chain variable gene segment (VH) invades a pre-existing rearrangement (VDJ). In this Hypothesis and Theory article, we begin by reviewing the mechanism of VH replacement, its developmental timing and its potential biological consequences. Then we explore the hypothesis that specific sequence motifs called footprints reflect VH replacement vs. other processes. We provide a compilation of footprint sequences from different regions of the antibody heavy chain, include data from the literature and from a high throughput sequencing experiment to evaluate the significance of footprint sequences. We conclude by discussing the difficulties of attributing footprints to VH replacement.